Corporate Social Responsibility of PT. Kalimantan Sawit Kusuma to Improves Local People Welfare - Alexandro, Rinto; Oktaria, Merisa (Universitas Pendidikan Ganesha, 2020)
Corporate Social Responsibility (CSR) is a form of commitment, concern and responsibility of the company to the external environment of the company through various activities. This research aims to analyze the impact of CSR implementation on the welfare of local communities. Data analysis using the Spradley model of domain analysis, taxonomy and components, cultural theme analysis. The results of the research stated that PT. KSK has implemented CSR programs in the field of education, that is providing scholarships and giving goods of stationery equipment, as well as assistance for village libraryÂ and carried out gradually. In the field of health that is building clean water drill wells, building posyandu and free health checks and carrying out CSR programs in the field of infrastructure, that is by carrying out repairs of village's road and village's waterway (drainase). With the implementation of csr program, balai riam sub-district community feels much better than before, but for the recruitment of the surrounding community to be part of PT. KSK is still not fully implemented because the level of education owned by the surrounding community is still low and does not meet the criteria of hr recruitment of PT. KSK. So this research has social implications that play a role in improving the progress of people's lives around the company.